Penguatan Peran Ibu sebagai Madrasatul Ula untuk Pencegahan Bullying pada Anak dan Remaja di Fatayat Nu Ranting Dilem - Fitroturohmawati Fitroturohmawati; Aries Musnandar (Indo Publishing, 2026)
Bullying among children and adolescents is a social and educational issue that seriously impacts their social, emotional, and psychological development. Bullying prevention efforts require a comprehensive approach, involving the family as the primary educational environment, particularly mothers as primary educators. This Community Service activity aims to strengthen the role of mothers in bullying prevention by increasing understanding, awareness, and parenting skills oriented toward character building in children. The implementation method uses a brief educational approach based on interactive dialogue, beginning with the presentation of material on the concept of bullying, its forms and characteristics, and its impact on child development. This is followed by a participatory discussion and question-and-answer session. This activity is also supported by the distribution of printed media in the form of leaflets or pocket books as practical guides and to strengthen motivation to encourage the ongoing implementation of positive parenting. The results of the activity indicate an increase in mothers' understanding and awareness in recognizing bullying behavior, the importance of family communication, and the implementation of warm, responsive, and consistent parenting as a preventative measure. The participants' active participation in the discussion resulted in contextual and applicable parenting solutions and fostered mothers' commitment to acting as agents of bullying prevention within the family and community. Thus, this activity confirms that strengthening the role of mothers as madrasahul ula through a simple and participatory educational approach is an effective and efficient strategy for building a family- and community-based bullying prevention system.